(untitled) (Interdisciplinary Studies Journal, 2024)
This paper proposes a reading of Brazil starting from the exchange dual dialogue of north and south, old and new world, situated in the fake news and the new health crisis, caused by COVID-19, in this effort. The study is based on the contributions of three fields of knowledge: History, Literature and Politics. The qualitative methodology uses the descriptive and exploratory tool, sustained by a bibliographic review, doing therefore a panoramic framework that converges interdisciplinarily the relations proposed in the aim, giving opportunity to reflections that allow the first debates of the landmark that represents the world sanitary crisis and its effects in Brazil.